Failure rate in the untreated contralateral node negative neck of small lateralized oral cavity cancers: A multi-institutional collaborative study. (April 2021) - Liu, Howard Yu-hao; Tam, Laura; Woody, Neil M.; Caudell, Jimmy; Reddy, Chandana A.; Ghanem, Ahmed; Schymick, Matthew; Joshi, Nikhil; Geiger, Jessica; Lamarre, Eric; Burkey, Brian; Adelstein, David; et al.
Highlights: Large cohort of small lateralized oral cancers that received unilateral treatment. 5-year incidence of contralateral neck failure was low at 4.3%. Depth of invasion >10 mm associated with increased contralateral neck failure risk. In well selected patients, the contralateral node negative neck can be observed. Consider treating the bilateral neck in small but deeply invasive oral cancers. Abstract: Objectives: The importance of treating the bilateral neck in lateralized small oral cavity squamous cell carcinoma (OCC) is unclear. We sought to define the incidence and predictors of contralateral neck failure (CLF) in patients who underwent unilateral treatment. Materials and methods: We performed a multi-institutional retrospective study of patients with pathologic T1-T2 (AJCC 7th edition) OCC with clinically node negative contralateral neck who underwent unilateral treatment with primary surgical resection ± adjuvant radiotherapy between 2005 and 2015. Incidence of CLF was estimated using the cumulative incidence method. Clinicopathological factors were analyzed by univariate (UVA) and multivariate analysis (MVA) for possible association with CLF. Kaplan-Meier analysis was used to estimate overall survival (OS). Results: 176 patients were evaluated with a median of 65.9 months of follow-up. Predominant pathologic T-stage was T1 (68%), 8.5% of patients were N1, 2.8% were N2b. Adjuvant radiotherapy was delivered to 17% of patients. 5-year incidence of CLF was 4.3% (95% CI 1.2–7.4%). Depth of invasion (DOI) > 10 mm and positive ipsilateral neck node were significant predictors for CLF on UVA. DOI > 10 mm remained significant on MVA (HR = 6.7, 95% CI 1.4–32.3, p = 0.02). The 2- and 5-year OS was 90.6% (95% CI 86.2–95.0%) and 80.6% (95% CI 74.5–86.8%), respectively. Conclusion: Observation of the clinically node negative contralateral neck in small lateralized OCC can be a suitable management approach in well selected patients, however caution should be applied when DOI upstages small but deeply invasive tumors to T3 on 8th edition AJCC staging.